Big copyright versus the people : how major content providers are destroying creativity and how to stop them / Martin Skladany. - Skladany, Martin (Cambridge University Press, 2018)
When the idea of copyright was enshrined in the Constitution it was intended to induce citizens to create. Today, however, copyright has morphed into a system that offers the bulk of its protection to a select number of major corporate content providers (or Big Copyright), which has turned us from a country of creators into one of consumers who spend, on average, ten hours each day on entertainment. In this alarming but illuminating book, Martin Skladany examines our culture of overconsumption and shows not only how it leads to addiction, but also how it is unraveling important threads - of family, friendship, and community - in our society. Big Copyright versus the People should be read by anyone interested in understanding how Big Copyright managed to get such a lethal grip on our culture and what can be done to loosen it.